Endogenous pensions and retirement behavior - Randall Filer; Marjorie Honig (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper suggests that pension characteristics are simultaneously determined along with workers? retirement ages. Both the age of pension eligibility and actual retirement age are determined by the productivity and marginal disutility of work, factors that are influenced by worker and job characteristics. This approach differs from previous studies of retirement that treat pensions as exogenous, implying that prior empirical work may have overestimated the responsiveness of retirement age to changes in pension structure, a possibility with obvious policy implications for efforts to raise the age of retirement. We find that, in the conventional single-equation framework, delaying the age of pension eligibility would significantly delay retirement. When treated in a recursive simultaneous system, however, age of pension eligibility retains no explanatory power.
Keywords: H55; H31; J26; 330; social security; early retirement; job characteristics; pension eligibility; Altersgrenze; Arbeitsangebot; Arbeitsproduktivität; Schätzung; Theorie; USA